The Influence of Job Satisfaction and Work-Life Balance on Turnover Intentions: A Study of Generation Z Employees in the Hospitality Industry of Dili, the Capital of Timor-Leste - Soares, Cesaltino Sarmento; Putri, Ratna Komala (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the influence of job satisfaction and work-life balance on turnover intentions in Generation Z employees in the hospitality industry in Dili City, Timor-Leste. The research method used a quantitative approach with a purposive sampling technique involving 202 respondents. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of SmartPLS version 4. The results showed that job satisfaction had a positive and significant effect on turnover intentions with a path coefficient of 0.296 (t-statistic = 3.330; p-value = 0.001). In contrast, work-life balance had no significant effect on turnover intentions with a path coefficient of 0.011 (t-statistic = 0.406; p-value = 0.685). The research model has an R² value of 0.959, indicating that 95.9% variability of turnover intentions can be explained by both independent variables. The findings indicate that even though employees are satisfied with their work, they still have a tendency to look for new job opportunities that are more in line with personal aspirations. This research makes a theoretical contribution to understanding the work behavior of Generation Z and its practical implications for human resource management in the hospitality sector.